Pengaruh Kepemimpinan Transformasional dan Motivasi Kerja terhadap Kinerja Personel TNI AD di Pusat Pendidikan Artileri Medan - Pangestuti, Monika Windiana; Sari, Rini Mulyani (Ekonomis: Journal of Economics and Business, 2025)
This study aims to analyze the influence of transformational leadership and work motivation on the performance of Indonesian Army Personnel at the Medan Artillery Education Center (Pusdikarmed). This study uses a quantitative approach with a survey technique by distributing questionnaires to Indonesian Army Personnel at the Medan Artillery Education Center. The data were analyzed using SPSS software to test the relationship and influence between the variables of transformational leadership, work motivation, and performance. The results of the study indicate that simultaneously and partially, transformational leadership and work motivation have a strong and significant influence on the performance of Indonesian Army Personnel at the Medan Artillery Education Center